2005
DOI: 10.1002/mrd.20223
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting production of transgenic rats by ICSI-mediated DNA transfer: Effects of sonication and freeze-thawing of spermatozoa, rat strains for sperm and oocyte donors, and different constructs of exogenous DNA

Abstract: Factors affecting the efficiency of producing transgenic rats by intracytoplasmic sperm injection (ICSI)-mediated DNA transfer were investigated. Epididymal spermatozoa from Sprague-Dawley (SD) rats were sonicated and/or frozen-thawed for cutting the tail and membrane disruption. The sperm heads were exposed for 1 min to different concentrations (0.02-2.5 microg/ml) of 3.0 kb enhanced green fluorescent protein (EGFP) DNA solution, and then microinjected into the denuded F1 hybrid (Donryu x LEW) rat oocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
48
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
1
48
0
2
Order By: Relevance
“…This result agreed well with our previous report that ICSI after exposure to 5 ng/µl DNA resulted in no development beyond the 4-cell stage in vitro [7]. However, even with the protection of RecA-coating, there was no EGFP-carrying transgenic rat among the 26 newborn offspring produced by this procedure.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…This result agreed well with our previous report that ICSI after exposure to 5 ng/µl DNA resulted in no development beyond the 4-cell stage in vitro [7]. However, even with the protection of RecA-coating, there was no EGFP-carrying transgenic rat among the 26 newborn offspring produced by this procedure.…”
supporting
confidence: 93%
“…In general, the proportion of microinjected zygotes developing into transgenic offspring is <5% in rodents [1,5], and <1% in large domestic species [17,22]. Another approach to production of transgenic animals is intracytoplasmic sperm injection (ICSI)-mediated transgenesis (ICSI-Tg) [16], in which <7% of inseminated oocytes develop into transgenic mice [16,20] and rats [7,9]. Maga et al [11] recently reported that recombinase-A protein (RecA)-coated ssDNA was more likely to be integrated into goat and pig genomes after pronuclear microinjection (6-and 10-fold higher, respectively).…”
mentioning
confidence: 99%
See 3 more Smart Citations